Principles and Measures of Watershed Management in China - Lixian, Wang (Annals of Arid Zone, 2016)
China has only 7% of the world's arable land, but feeds 22% of the world population. The country ranks 88th in the world in per capita water availability, and an imbalance exists between population and availability of land and water. In order to protect, improve and rationally use the water, land and other natural resources, the Chinese Government pays great importance to integrated watershed management. This paper presents the concept, principles and measures of watershed management in China, as well as the achievements and experiences gained since the founding of the People's Republic of China. Watershed management policies are the basis of watershed management. Yet, the economic policies and laws and regulations of watershed management in China have major problems. Several effective counter-measures in watershed management have been discussed, including: (i) perfection of management systems of watershed; (ii) maintenance of long-term stability of various management systems; (iii) annual fund allocation by the central and local governments to support watershed management and make detailed financial support policies; and (iv) establishment of social service systems for watershed management.